Pengaruh Aditif Limbah Kerang Darah (Anadara Granosa) Terhadap Kualitas Beton K-225 - Dian Kharismadewi; Muhammad Afrizal Pelantika; Marhaini (Jurnal INOVATOR, 2022)
A rapid development of the concrete construction sector has resulted in an increase in the need for concrete raw materials that are obtained directly from nature. The need for environmentally friendly materials is also increasing along with the development of construction engineering technology, so several studies have been conducted to search for an alternative to raw materials additives or concrete mixtures. Anadara granosa clam shell can be utilized as one of the alternative materials to substitute material for coarse aggregates. In this research, Anadara granosa clam shells of 10% and 13% were added to normal concrete mixtures, aged for 28 days, and then analyzed for characteristics and compressive strength. From the analysis of the results, it was found that an increase in the concrete compressive strength up to 103.67% or 233.47 Kg/cm2 with the addition of clam shells 10% to normal concrete mixtures, while the addition of more than 10% can reduce the concrete compressive strength. Scanning Electron Microscopy results showed a relatively rough surface and many pores on the surface of the concrete due to the addition of a clam shell. Finally, it can be concluded that Anadara granosa clam shells can be used as concrete additives with a maximum addition of 10% of the total weight of normal concrete.